Presence of microorganisms in commonly used baby cosmetics, available in Dhaka City (Stamford Journal of Microbiology, 2020)
Cosmetics especially baby products should be safe as children are immunocompromised which means their immune system is not developed enough to combat infections caused by the presence of any pathogenic bacteria. Different factors like chemical composition of cosmetics, handling and storage conditions can influence the chance of contamination of cosmetic products. This study aimed to evaluate the microbiological quality of different commercially available baby cosmetics such as body lotion, body wash or soap, baby shampoo, baby oil of different popular brands sold in Dhaka city. In the current investigation four different brands of cosmetics were subjected to bacteriological and mycological screening. Total viable bacteria and fungal load in all the samples of Brand 1 was in average of 105 cfu/g which exceeded the acceptable limit. The samples were found to contain pathogenic bacteria as well, especially Klebsiella spp. The findings indicate that the quality Brand 1 products were not satifactory and might cause harm to children and other consumers. Microbial load of other brands fell within the acceptable limit which indicate their good quality. The incidence of microorganisms in Brand 1 might be due to contamination during the production process or storage under unhygienic condition. Therefore in order to avoid infections in children due to microbial contamination of cosmetics items it is essential to take precautions during production process and storage in appropriate conditions and avoiding use of cosmetics products on damaged skin.Stamford Journal of Microbiology, Vol.9(1) 2019: 9-11